2023
DOI: 10.1111/1468-5973.12482
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the efficacy of instructing and adjusting information: An exploration of interactivity and vividness

Abstract: Instructing and adjusting information is required to protect stakeholders during a crisis. However, it is unwise to assume that people, especially young adults, automatically follow the information once it is provided. Using a 2 (interactivity: low [email] vs. high [mobile app]) × 2 (vividness: low [text‐only] vs. high [infographic]) between‐subject lab experiment, this study found that infographics were effective in improving self‐efficacy, proxy efficacy, and trust in the organization. In addition, an intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
(177 reference statements)
0
1
0
Order By: Relevance
“…An important challenge is therefore to develop warning messages that are brief enough for people to be able to take in the information, but long enough to reduce milling, thus shortening warning response delays [40]. Zhou et al [41] found evidence of the advantage of using information graphics, i.e., different formats of data visualisation in crisis communication. For example, combinations of time-and action-related icons with hazard messages have been found to increase people's intentions to act in hazardous situations [42].…”
Section: Public Warnings: Channels Of Emergency Communicationmentioning
confidence: 99%
“…An important challenge is therefore to develop warning messages that are brief enough for people to be able to take in the information, but long enough to reduce milling, thus shortening warning response delays [40]. Zhou et al [41] found evidence of the advantage of using information graphics, i.e., different formats of data visualisation in crisis communication. For example, combinations of time-and action-related icons with hazard messages have been found to increase people's intentions to act in hazardous situations [42].…”
Section: Public Warnings: Channels Of Emergency Communicationmentioning
confidence: 99%